THU0072 Distribution of selective matrixins, timp-1, cytokines. (1st June 2001) - Stovickova, J; Hulejova, H; Pesakova, V; Adam, M
Abstract : Background: The most abundant joint disease is osteoarthritis. Recently it was classified as cartilagenous, synovial or osseous but the unique forms may be combined. The main feature of the disease is imbalance between synthetic and degradative processes within joint tissues. Executive part in degradative processes play matrix metalloproteinases, so called matrixins. In situ, they are induced by many stimuli, namely by cytokines and by interaction of different adhesive molecules with their ligands. Having been secreted into the extracellular space, they are activated by serine proteinases, or by other matrixins and inhibited by tissue inhibitors of matrix metalloproteinases, TIMPs. Objectives: Methods: In the sera of OA patients we found matrixins MMP-9, MMP-2 and MMP-3 and TIMP-1 together with cytokines IL-8 and TNF/alpha and adhesive molecules ICAM-1 and VCAM-1. To distinguish between the forms of osteoarthritis, we search for these molecules in all joint tissues that is in cartilage, synovium, granulation tissue, within subchondral bone, synovial fluid and blood serum. The joint tissues and fluids we obtain from surgery during total hip or knee replacement. Results: The joint tissues were derived from 22 patients. We obtained 10 samples of knee joints and 12 samples of hip joints. The patients were 17 female and 6 male, 67, 5 ± 9, 6 years old, age ranges 48–86 years. The metalloproteinase spectrum in the body fluids and extracts of joint tissues were evaluated by zymography. The concentration of metalloproteinases and TIMP-1 were assessed by ELISA (Biotrak, Amersham Pharmacia Biotech), the concentration of adhesive immunoglobulins by Bender ELISA (MedSystems Diagnostics GmbH), and the concentration of IL-8 and TNF/alpha were determined on Immulite (DPC, USA). We found that the most abundant matrixine within cartilage and synovium is either gelatinase A (MMP-2) or stromelysine-1 (MMP-3). On the other hand, within granulation tissue, blood sera and synovial fluid, the prevailing matrixine is gelatinase B or stromelysine-1. In cartilage, synovial fluid and blood serum TIMP-1 is abundant over sum of matrixins, whereas in synovium and granulation tissue the sum of matrixins is abundant over TIMP-1. There is about 2 to 10 times greater concentration of IL-8 in the cartilage than in other joint compartments. We found significant correlation between levels of sICAM-1 and sVCAM-1, between TNF/alpha and MMP-3, TIMP-1, sICAM-1, sVCAM-1, and IL-8, and between IL-8 and sICAM-1 in all solid joint tissues. In the synovial fluid and blood serum the correlation was less pronounced. Conclusion: There is a great degradative potential within all compartments of osteoarthritic joint due to presence of matrixins, namely that of stromelysin-1. Within cartilage and synovial fluid the proteolytic potential is equilibrated by TIMP-1 whereas within synovium and granulation tissue is not. Synovium and granulation tissue are highly probably the propellers of degradative process in osteoarthritis. Rheumatoid Arthritis – Aetiology and pathogenesis/Animal models